Enhancing Student Motivation and Learning Outcomes Through Teams Games Tournament Integration with Wordwall - Wahidatul Munandar; Yusminah Hala; Syamsiah Syamsiah (Papanda Publisher, 2026)
This quasi-experimental study investigated the differential effects of Teams Games Tournament (TGT) learning model with and without Wordwall integration on eleventh-grade biology students' motivation and learning outcomes at SMAN 8 Gowa, Indonesia. Seventy-two students were assigned to two experimental groups: R1 (TGT with Wordwall, n=36) and R2 (TGT only, n=36). Data were collected using a 20-item motivation questionnaire and a 30-item achievement test administered as pretests and posttests. Statistical analyses included descriptive statistics, one-way ANOVA, and normalized gain (N-Gain) calculations. Results revealed significant differences favoring TGT-Wordwall integration for both motivation (F(1,70)=38.42, p<.001, η²=.354) and learning outcomes (F(1,70)=86.77, p<.001, η²=.554). The R1 group achieved high N-Gain scores (g=0.78 for motivation; g=0.82 for learning outcomes) compared to R2's moderate gains (g=0.50 and g=0.63 respectively). Categorical analysis showed 66.7% of R1 students reached adequate or good performance levels versus only 8.3% in R2. These findings demonstrate that integrating interactive digital platforms with cooperative learning models substantially amplifies instructional effectiveness. The study provides empirical evidence supporting technology-enhanced pedagogy in secondary education and offers practical implications for educators implementing 21st-century learning approaches in biology instruction.